2018
DOI: 10.1007/s12040-018-0933-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of straw mulching on soil evaporation during the soil thawing period in a cold region in northeastern China

Abstract: To study the effect of straw mulching on soil water evaporation, it is necessary to measure soil water evaporation under different conditions of straw mulching during the soil thawing period. A field experiment was conducted in winter, and soil evaporation was measured using a microlysimeter on bare land (LD) and 4500 (GF4500), 9000 (GF9000) and 13500 kg/hm 2 (GF13500) straw mulch. The influence of different quantities of straw mulch on soil water evaporation during the thawing period was analyzed using the Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Thus solar radiation and air temperature became the major factors influencing soil evaporation in P3 for all treatments. In P3, straw mulch delayed the thawing rate of surface soil because the soil temperature gradient and soil heat transfer under straw mulch were smaller than those for BS treatment [37]. The direct absorption of solar radiation by soil was hindered and the soil temperature rose slowly under straw mulching, so the surface soil temperature was the other major factor that influenced soil evaporation in J1, J2, and J3 treatments.…”
Section: Thawing Stagementioning
confidence: 98%
See 2 more Smart Citations
“…Thus solar radiation and air temperature became the major factors influencing soil evaporation in P3 for all treatments. In P3, straw mulch delayed the thawing rate of surface soil because the soil temperature gradient and soil heat transfer under straw mulch were smaller than those for BS treatment [37]. The direct absorption of solar radiation by soil was hindered and the soil temperature rose slowly under straw mulching, so the surface soil temperature was the other major factor that influenced soil evaporation in J1, J2, and J3 treatments.…”
Section: Thawing Stagementioning
confidence: 98%
“…Straw mulching reduced the freezing depth of soil and changed the natural variation of soil water and heat during the freezing-thawing period [36]. Straw mulch delayed the thawing of the surface soil by 3 to 6 days, reduced cumulative evaporation and the range of soil evaporation [37]. Fu et al [37] determined the effects of straw mulching on soil water evaporation in the Songnen Plain during the thawing period, while the effect of the freezing period was not shown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Vargas et al (2014) 2017) demonstrated the highest N 2 O emissions from soils at a WFPS between 50% and 70%, which alters soil aeration and gas diffusion and thus influences O 2 availability for microbial activity in soil. Furthermore, one indirect effect of mulch on the water dynamics in soil is its effect on soil temperature, which modifies evaporation rates among straw levels (Fu et al 2018). In general, our results showed a wide temperature range (between 09:00 and 11:00, the time of N 2 Om e a s u r ements) in soil with no or low amounts of straw (0S and 4S), which varied from 21°C to 35°C, whereas for the 8S and 12S treatments, the maximum temperature did not exceed 30°C, which confirmed the role of the mulch as a buffer against climate fluctuations in the soil.…”
Section: Effects Of Straw On N 2 O Emissionsmentioning
confidence: 99%
“…Frozen soil evaporation is affected by groundwater table depth, solute content (Wu et al, 2016) and surface mulching (Feng et al, 2018; Fu, Yan, Li, Cui, & Peng, 2018). Studies have explored the effects of straw mulch on soil moisture conservation and soil evaporation during the thawing period via field experiments (Fu et al, 2018), revealing the major factors that influence soil evaporation in different freeze–thaw stages (Chen et al, 2019). Regarding sand mulch, Feng et al (2018) assessed the impact of particle size (0.5–1.5 and 1.5–2.0 mm) on soil evaporation during a freeze–thaw period in Northern China; however, how sand‐mulch thickness affects soil evaporation in cold regions remains unclear.…”
Section: Introductionmentioning
confidence: 99%